Green synthesis of silver and gold ultra nanocomposites from silk fibroin and their application for treatment of endodontic infections - Pramod C.; Pawar, Jayant; Mane, Deepali P.; Khadase, Ashok N.; Chaudhari, Aditya R.; Ughade, Supriya P.; Chaudhari, Ravindra D.; Agawane, Sachin B. (Emergent Materials, 2024)
The present study is designed to investigate the antibacterial efficacy of B. mori silk fibroin based silver and gold ultra bio-nanocomposites (SF-AgUNC and SF-AuUNC) against Enterococcus faecalis for endodontic disinfection. The SF-AgUNC and SF-AuUNC based irrigant solution was tested in- vitro against Enterococcus faecalis (ATCC: 29212). In this direction, SF-AgUNC and SF-AuUNC synthesized by silk fibroin are very important as they are economically cheap and easy to biosynthesize. The synthesis of SF-AgUNC and SF-AuUNC was accomplished by dissolving 1 mM silver nitrate and 0.5 mM auric chloride respectively in 10 ml of fibroin as precursors. The structural and morphological analysis was executed by UV-Vis Spectroscopy, X-ray diffraction (XRD), Fourier transform infrared spectroscopic analysis (FTIR), Field Emission Scanning Electron Microscopy (FESEM), Transmission electron microscopy (TEM), Energy-dispersive X-ray spectroscopy (EDAX) and X-ray photoelectron spectroscopy (XPS). The qualitative antimicrobial activity of SF-AgUNC and SF-AuUNC were performed against inoculum of Enterococcus faecalis containing 1⨯105 CFU/ ml. The same solutions were tested on dentine specimens inoculated with bacterial cultures and found remarkable biofilm reduction. The structural and morphological analysis reveals the formation of SF-AgUNC and SF-AuUNC having quasi-spherical morphology. The average particle size for SF-AgUNC and SF-AuUNC was same (~ 8 nm). The XRD study confirms that, both SF-AgUNC and SF-AuUNC were crystalline in nature. The bacterial growth inhibition and significant biofilm reduction was observed on dentine specimens treated with SF-AgUNC, SF-AuUNC and positive control. In antibacterial study, at 30 μg/well concentration of SF-AgUNC and SF-AuUNC, 3.13 ± 0.22 and 1.13 ± 0.22 cm of zone of inhibition was noted respectively. Moreover, growth of Enterococcus faecalis was completely inhibited at 20 μg/ml and 30 μg/ml when treated with SF-AgUNC and SF-AuUNC respectively. Hence, the present study concludes that SF-AgUNC and SF-AuUNC can be used as an effective intracanal medicament for the treatment of dental problems with no cyto toxicity.